Factors Influencing PUS Women on the Selection of Long-Term Contraceptive Methods (MKJP) at Puskesmas MON Geudong Kec. Banda Sakti Lhokseumawe City - Nurmega Nurmega; Sarma Nursani Lumbanraja; Ramadhani Syafitri Nasution (PROMOTOR, 2024)
The Family Planning (KB) program is crucial in efforts to control birth rates, improve family welfare, and reduce maternal, infant and child mortality rates. This article highlights the implementation of family planning in Indonesia, the focus is on the selection of Long-Term Contraceptive Methods (MKJP) at the Mongeudong Health Center, Banda Sakti District, Lhoksemauwe City in 2023. Through an analytical survey, data from 95 respondents of women of childbearing age who use family planning were analyzed, including characteristics, knowledge, attitudes, husband's support, socio- cultural aspects, and MHJP selection. The results show that the majority of respondents have good knowledge and positive attitudes, but their husbands' support and socio- cultural conditions are less supportive, and the majority do not choose MHJP. The analysis shows a significant relationship between knowledge, attitudes, husband's support, socio-cultural conditions, and MHJP selection. These variables have a strong influence on the selection of MHJP. However, the role of health workers does not appear significant in the context of MHJP selection in this study.